Self-monitoring and job performance: The moderating role of tenure - Moser, Klaus; Galais, Nathalie (International Journal of Selection and Assessment, 2007)
Previous research on the relationship between self-monitoring and job performance has neglected the role of tenure even though both theory and preliminary evidences suggest that job incumbents' tenure should be a strong moderator. The current study investigates the role of organizational tenure on the relationship between self-monitoring and job performance (number of new contracts sold) in a sample of sales insurance agents. Consistent with expectations, tenure moderates the relationship between self-monitoring and job performance, i.e., self-monitoring is positively correlated with job performance for job incumbents with less tenure but not for those with more tenure. We propose that the relationship between self-monitoring and job performance depends on the job incumbents' ability and opportunity to control the cues available to those who interact with and/or appraise the performance of the job incumbent.